2019
DOI: 10.2903/j.efsa.2019.5714
|View full text |Cite
|
Sign up to set email alerts
|

EFSA statement on the review of the risks related to the exposure to the food additive titanium dioxide (E 171) performed by the French Agency for Food, Environmental and Occupational Health and Safety (ANSES)

Abstract: On 15 April 2019, the French Agency for Food, Environmental and Occupational Health and Safety (ANSES) published an opinion on the risks related to the exposure to the food additive titanium dioxide (E 171) taking into account the most recent scientific studies available. Further to this publication, EFSA was requested by the European Commission to provide urgent scientific and technical assistance regarding the opinion issued by ANSES. In the ANSES opinion, 25 new relevant publications published between 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…More recently, Talamini et al showed that the repeated administration of E171 to mice resulted in TiO 2 deposition in the gastrointestinal tract and the liver, and it is associated with molecular and cellular alterations in the inflammatory response [48]. In addition, the French Agency for Food, Environmental, and Occupational Health and Safety (ANSES) proposed that titanium dioxide should be considered as being potentially carcinogenic to humans when inhaled, but there was no carcinogenic concern for oral and dermal exposure [49][50][51]. These studies urged relevant governmental agencies to reassess the safety of titanium dioxide as a food additive.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Talamini et al showed that the repeated administration of E171 to mice resulted in TiO 2 deposition in the gastrointestinal tract and the liver, and it is associated with molecular and cellular alterations in the inflammatory response [48]. In addition, the French Agency for Food, Environmental, and Occupational Health and Safety (ANSES) proposed that titanium dioxide should be considered as being potentially carcinogenic to humans when inhaled, but there was no carcinogenic concern for oral and dermal exposure [49][50][51]. These studies urged relevant governmental agencies to reassess the safety of titanium dioxide as a food additive.…”
Section: Introductionmentioning
confidence: 99%
“…In April 2019, the French Agency for Food, Environmental and Occupational Health and Safety (ANSES) published a review suggesting a genotoxic and carcinogenic potential even if further in vivo mammalian studies are warranted to confirm or rule out these hypotheses [ 12 ]. As requested by the European Commission, EFSA provided urgent scientific and technical review regarding the opinion issued by ANSES [ 13 ]. The EFSA concluded that the latest ANSES opinion does not identify any major new findings that would overrule the conclusions made in the previous two scientific opinions in 2016 and 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, there is no consensus on the use of TiO 2 as a food additive. The European Food Safety Authority (EFSA) Panel on "Food Additives and Nutrient Sources Added to Food" stated that the food additive E171 containing TiO 2 (anatase or rutile structure) does not raise a genotoxic concern [10,11]. However, other regulatory bodies such as the French Agency for Food, Environmental and Occupational Health and Safety (ANSES) have emphasized the need to conduct studies to fully characterize the potential health effects related to ingestion of this food additive [12], leading to the ban of its use in food in France, since January 2020.…”
Section: Introductionmentioning
confidence: 99%